Orthogonality Relations for Multivariate Krawtchouk Polynomials - Mizukawa, H. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
The orthogonality relations of multivariate Krawtchouk polynomials are discussed. In case of two variables, the necessary and sufficient conditions of orthogonality is given by Grünbaum and Rahman in [SIGMA 6 (2010), 090, 12 pages]. In this study, a simple proof of the necessary and sufficient condition of orthogonality is given for a general case.